1996
DOI: 10.1111/j.1749-6632.1996.tb53510.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Resistance of Creole Goats to Cowdriosis in Guadeloupe Status in 1995

Abstract: A genetic predisposition to resistance (R)/susceptibility (S) has been demonstrated for cowdriosis in certain goal lines. In order to identify genetic markers of R/S and to follow their transmission to the offspring, 4 groups of sires and dams were crossbred in 1991, 1992, and 1993: Rr, RS, SR, and SS. The offspring were challenged at the age of six months with subsequent challenge of the S parent. From 28 presumed S dams, 7 turned out R and from 2 presumed S sires, 1 was R and the other undefinable. The resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The difference of allele frequencies at the MHC class II loci, DRBP1 and DYA, between the resistant and susceptible groups in the Cowdriosis population study indicated a possible influence of the MHC region as we also demonstrated by serological MHC class I typing in a previous study [4]. The detected association could not be demonstrated in family material up to now.…”
Section: Cowdriosismentioning
confidence: 49%
See 3 more Smart Citations
“…The difference of allele frequencies at the MHC class II loci, DRBP1 and DYA, between the resistant and susceptible groups in the Cowdriosis population study indicated a possible influence of the MHC region as we also demonstrated by serological MHC class I typing in a previous study [4]. The detected association could not be demonstrated in family material up to now.…”
Section: Cowdriosismentioning
confidence: 49%
“…For the Cowdriosis study, a total of 82 unrelated (37 classified resistant, 45 susceptible) experimentally challenged animals [4] with Cowdria ruminantium were tested. In the nematode resistance study, a total of 155 multiparous, lactating French alpine goats (2-4 years old) were naturally pasture-infected, predominantely with the parasite Trichostrongylus colubriformis.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of goat MHC class I proteins has been linked to resistance to the caprine arthritis-encephalitis virus infection, a disease that causes joint inflammation and lameness in adults and encephalitis in kids [112]. Other diseases where MHC polymorphisms may play an important role in the development of an appropriate immune response are cowdriosis [113,114], trichostrongyliasis [115], and Johne's disease [116]. It should be emphasized, however, that the immunological basis of these associations has not been elucidated yet.…”
Section: Genetic Determinants Of Disease Susceptibilitymentioning
confidence: 99%